Synthesis, spectroscopic and thermal characterization of quinoxaline metal complexes - Badawy, Mohamed Ahmed; Mohamed, Gehad Genidy; Omar, Mohamed Mohamed; Nassar, Mamdouh Mohammed; Kamel, Ahmed Badr (European Journal of Chemistry, 2010)
The coordination behaviour of the quinoxaline ligand with N and O donation sites, derived from 3-(2-oxo-2-p-tolylethyl)quinoxalin-2(1H)-one (HL), towards some transition metal ions namely Mn(II), Fe(III), Co(II), Ni(II), Cu(II) and Zn(II) are reported. The metal complexes are characterized based on elemental analyses, IR, 1H NMR, solid reflectance, magnetic moment, molar conductance and thermal analyses (TG, DTG and DTA). The ionization constants of the quinoxaline ligand as well as the stability constants of its metal chelates are calculated spectrophotometrically at 25 oC and ionic strength = 0.1 M (1M NaCl). The chelates are found to have octahedral structure. The ligand and its chelates are subjected to thermal analyses and the different activation thermodynamic parameters are calculated from their corresponding DTG curves to throw more light on the nature of changes accompanying the thermal decomposition process of these compounds. The biological activity of the synthesized ligand and its metal complexes also are screened against the desert locust Schistocerca gregaria (Forsk) (Orthoptera-Acrididae) and its adult longevities. They showed remarkable biological activity.